2022
DOI: 10.1089/whr.2021.0071
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Black Immigrant Women on Mental Health: The Role of Stigma

Abstract: Background: Black immigrants are a major growing segment of the United States population. The intersection of race, gender, and migration places black immigrant women at the confluence of multiple social determinants of health, and thus, black immigrant women experience ongoing mental health disparities. Understanding their perspectives, mental health needs, and associated stigma is critical to promoting positive mental health outcomes. Methods: We conducted five focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This view may have both positive and negative ramifications for help seeking. For example, black immigrant women in the USA identified spiritual resources as both sources of support and sources of stigma in the community [47]. Religious and community leaders are well placed to provide information to the community, which allows for well-informed mentalhealth-related decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view may have both positive and negative ramifications for help seeking. For example, black immigrant women in the USA identified spiritual resources as both sources of support and sources of stigma in the community [47]. Religious and community leaders are well placed to provide information to the community, which allows for well-informed mentalhealth-related decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, the Swahili-speaking community mentioned formal sources of help less frequently. Sub-Saharan African migrants may have alternative views on the appropriateness of formal sources of help, which may stem from historical and current experiences of racism and discrimination, as well as mistrust in the cultural responsiveness of Western mental health services [31,47]. Seeking help from Western mental health services carries the risk of misunderstanding and stigmatisation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Eisenberg et al (2009) specifically found that personal stigma was highest among younger, Asian, international, and more religious students, and that it was associated with low levels of help-seeking. Self-stigma may impair the provider–patient relationship through concerns regarding cultural mistrust and perceived substandard care (Bamgbose Pederson et al, 2022). Consequently, minoritized individuals may rely on alternative forms of support, as sharing personal information with a therapist may be perceived as a failure of primary community support or a lack of willpower, leading to potential feelings of shame.…”
Section: Professional Mental Health Help-seeking Among Asian Americansmentioning
confidence: 99%
“…19 The emotional stress associated with migrating from one country to another can negatively impact one's perceived sustainability after migrating. Bamgbose Pederson et al 20 conducted focus groups with black immigrant women, soliciting their mental health perspectives. Participants reported that the loss of financial security and status after migrating to North America was related to increased feelings of not being welcome in their new country.…”
Section: Migration and Mental Healthmentioning
confidence: 99%